Fenomena Sains sebagai Alternatif Meningkatkan Kecakapan Hidup - Syahrial A; M. Sarjan; Joni Rokhmat; Kurniawan Arizona; Ramdhani Sucilestari; Khaerus Syahidi; Syamsuddin Syamsuddin; I Gde Mertha (Universitas Hamzanwadi, 2022)
Morals are very important, so Allah SWT sent his messenger to fix it. Morals, attitude and character positive are life skills. Life skills cannot be taught, they should be transmitted, so a model is needed to be imitated. Scientific phenomena have the potential to be a model. Nature saves a lot of messages from Allah SWT which, if digested, becomes knowledge. One of the scientific phenomena in nature that can be used as knowledge and improve life skills are butterflies and magnets. Literature study is used to analyze scientific phenomena from several aspects, namely 1) religion based on Al-Quran and Hadith, 2) scientific concepts of phenomena found in nature, 3) application in life, and 4) integration in life skills. Butterflies can be a model of the importance of self-control to be good and not give up quickly in the face of difficulties and the belief that with difficulties there is ease. Magnets become a model of unity, rhythm, agreement, strength will be achieved. Based on the analysis, it can be concluded that the creation of Allah SWT in nature in the form of scientific phenomena can be a model for improving life skills.